PENGARUH PENGUNGKAPAN MANAJEMEN RISIKO TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar pada Bursa Efek Indonesia tahun 2019) - Tanjung Budi Hapsari; Imam Ghozali (Diponegoro Journal of Accounting, 2022)
This study aims to investigate the relationship between enterprise risk management on firm value. The independent variable in this research is operational risk management, strategy risk management, integrity risk management, empowerment risk management, dan information processing technology risk management. While the dependent variable used in this study is firm value.This study uses secondary data from the financial information provided on Bloomberg database of companies listed on the Indonesian Stock Exchange. Using purposive sampling method, the 161 samples selected from manufactur sector which published its financial statements from 2019-2020. Multiple regression analysis is the test used to study the relationship between operational risk management, strategy risk management, integrity risk management, empowerment risk management, dan information processing technology risk management on firm value.The results show that operational risk management, strategy risk management, , empowerment risk management, dan information processing technology risk management  may be an organizational device that has positive and significant impact to firm value.